2016
DOI: 10.1266/ggs.15-00056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of microRNA profiles of rice anthers between cool-sensitive and cool-tolerant cultivars under cool-temperature stress

Abstract: Plants subjected to abiotic stress can regulate gene expression post-transcriptionally by means of small RNAs such as microRNAs. Cool-temperature stress causes abnormal tapetum hypertrophy in rice anthers, leading to pollen sterility. As a first step toward understanding the molecular mechanisms of cool tolerance in developing anthers of rice, we report here a comprehensive comparative analysis of microRNAs between cool-sensitive Sasanishiki and cool-tolerant Hitomebore cultivars. High-throughput Illumina sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Consistently, after 3 days recovering, most of the OXmiR397 seedlings survived while most of the WT seedlings died ( Figure 4G ). It has been reported that miR397 is induced by different stresses in various species (Sunkar and Zhu, 2004; Wang et al, 2013; Maeda et al, 2016). Thus OsmiR397 regulated OsLAC13 abundance might play a role in stress response by suppressing H 2 O 2 production in roots.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, after 3 days recovering, most of the OXmiR397 seedlings survived while most of the WT seedlings died ( Figure 4G ). It has been reported that miR397 is induced by different stresses in various species (Sunkar and Zhu, 2004; Wang et al, 2013; Maeda et al, 2016). Thus OsmiR397 regulated OsLAC13 abundance might play a role in stress response by suppressing H 2 O 2 production in roots.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, rice production is not only impacted by drought but also the influence of saline and alkaline conditions [52], cold stress [53], heavy metal pollution [17], etc. The miR393, miR396 and miR820 responded to the saline and alkaline stress [52].…”
Section: Discussionmentioning
confidence: 99%
“…Cheah et al (2015) showed that several miRNAs including osa-miR398, osa-miR397, osa-miR408-5p and osa-miR528-5p were upregulated in the drought-susceptible rice variety [59]. This was also true for in cool-tolerant rice (Hitomebore) under cool-temperature [60]. The interaction network showed that 4 transcription factors (TFs), OsbZIP18, OsbZIP23, OsMYB5P and OsERF141, were potential target genes of aforementioned miRNAs.…”
Section: Interaction Relationship Of Mirnas and Mrna In Response To Cmentioning
confidence: 84%
“…The effect of osa-miR528-3p has not been studied till now. Both osa-miR528 and osa-miR408 family members were differentially expressed in response to abiotic stresses, such as drought [59], low temperature [60], heavy metal [61] and plant defense responses (the reference is about drought) [62]. Cheah et al (2015) showed that several miRNAs including osa-miR398, osa-miR397, osa-miR408-5p and osa-miR528-5p were upregulated in the drought-susceptible rice variety [59].…”
Section: Interaction Relationship Of Mirnas and Mrna In Response To Cmentioning
confidence: 99%